Somatic embryogenesis of an early cotton cultivar - González-Benito, María Elena; Frota-Chagas Carvalho, Julita María; Pérez, César (Pesquisa Agropecuaria Brasileira, 1997)
Somatic embryogenesis in cotton has been previously reported in a limited number of genotypes, predominantly Coker cultivars. Before tissue culture techniques are widely applied to cotton improvement programs, regeneration must be possible for a broad range of genotypes. The aim of the present work was to develop a method to obtain somatic embryoids of an early cotton cultivar (Gossypium hirsutum L. race latifolium Hutch cv. CNPA Precoce 2) and their subsequent development. Callus induction was attempted with cotyledon and hypocotyl explants. These explants were cultured on MS medium supplemented with five concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D) and N6-(2-isopentenyl)-adenine (2iP) either alone or in combination. Based on callus appearance (light brown and granular), four different growth regulator combinations were selected for further callus development. Callus was subcultured on 2.45 μM 2iP and subsequently transferred to 0.45 and 22.50 μM 2,4-D. Somatic embryos of different sizes and shapes subsequently appeared on MS medium supplemented with 2 g L-1 glutamine and no growth regulators. Plantlets were developed from those embryoids. Plant regeneration through somatic embryogenesis is achieved for the first time in the early cultivar CNPA Precoce 2.